The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00125-021-05469-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition in the 2′-5′A pathway in the development of type 1 diabetes: potential contribution to dysregulation of innate antiviral immunity

Abstract: Aims/hypothesis The incidence of type 1 diabetes is increasing more rapidly than can be explained by genetic drift. Viruses may play an important role in the disease, as they seem to activate the 2′-5′-linked oligoadenylate (2′-5′A) pathway of the innate antiviral immune system. Our aim was to investigate this possibility. Methods Innate antiviral immune pathways were searched for type 1 diabetes-associated polymorphisms using genome-wide association study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“… Field et al (2005) proposed that OAS1 activation may promote β-cell apoptosis, thereby enhancing susceptibility to T1DM. Pedersen et al (2021 ) showed upregulation of OAS1 in the islets of T1DM. OAS1 is also relevant in multiple sclerosis, and hepatitis C virus infection ( García-Álvarez et al, 2017 ; O'Brien et al, 2010 ).…”
Section: Discussionmentioning
confidence: 95%
“… Field et al (2005) proposed that OAS1 activation may promote β-cell apoptosis, thereby enhancing susceptibility to T1DM. Pedersen et al (2021 ) showed upregulation of OAS1 in the islets of T1DM. OAS1 is also relevant in multiple sclerosis, and hepatitis C virus infection ( García-Álvarez et al, 2017 ; O'Brien et al, 2010 ).…”
Section: Discussionmentioning
confidence: 95%
“…multiple sclerosis or lupus erythematosus ( 6 ). It was reported to play a pivotal role in the development of both type 1 and type 2 diabetes in humans ( 6 , 20 , 24 , 30 ). Although the natural course of canine diabetes and its aetiopathogenesis are not exactly the same as in humans, there are numerous reports suggesting its similarity to type 1 diabetes, with the autoimmune response playing a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained activation of OAS or RNAse L may lead to protein translation arrest and cell apoptosis (Hornung et al, 2014). Indeed, polymorphisms in the OAS gene cluster have been associated with increased OAS enzymatic activity and susceptibility to T1D (Field et al, 2005;Pedersen et al, 2021;Tessier et al, 2006). Intriguingly, β-cells are unique among pancreatic islet cells with the ability to upregulate OAS expression in response to interferon-α or poly(I:C) (a dsRNA mimetic) (Bonnevie-Nielsen et al, 1996;Li et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%